Fatores de risco e consequências de quedas domiciliares entre idosos em um bairro de Belém - OLIVEIRA, Daiane Rodrigues de (2022)
The objective of this study was to describe the occurrence of the ambient factors and the inherent ones to the aging of risk for falls in aged, beyond the use of medicines and the specific diseases that contribute for this event, e its consequences. The present study it presents descriptive character, observational, transversal type. The data had been collected from the application of questionnaire to a group of 100 aged ones, residents in the quarter of the Umarizal (Belém-Pará), with history of one or more falls domiciliary in the period of January of 2004 the January of 2006. Such aged ones would have to more present 60 years or at the moment of the fall, having been fit in three groups: 60 to 69 years, the 70 to 79 years and 80 years or more. The studied sample was composed of 63% of aged of the feminine sex and the event fall revealed more frequent in the band of age of 60 to 69 years. The reduction of the vision was the inherent alteration to the found aging more, gift in 82% of this population, followed of alteration of the memory (54%) and of muscular weakness (50%). The observed specific diseases more had been the related ones to the cardiovascular device and the neurological one, corresponding 42% and 25.7% of the searched diseases. The interviewed medicines more used by the aged ones had been the antihypertensives, representing 35.5% of these. In the masculine sex, it was verified that 27% of the aged ones made use of five or more medicines, whereas the absence of the medicine use was not observed between these. In the feminine sex, the five more medicine or use was found in 16% of the participants and 9.5% of these did not make use of any medicine. The factor of domiciliary risk for aged falls between the most frequent one was the absence of railings in corridors and bathrooms, corresponding 24.3% of the total of the investigated ambient factors. One still verified the presence of slippery surfaces and the bad illumination in these domiciles, representing 16% and 10.7% of this group of factors, respectively. The consequences after fall had occurred in 57,1% of the individuals of the masculine sex and in 51,3% of the ones of the feminine sex. Of these, the decline of the activities of daily life had been observed followed for and the breakings and hospitalizations, corresponding 34.2% respectively, 27.8% and 20.2%. It is verified, therefore, the importance that must be attributed to the prevention of the falls through a boarding to multidiscipline of attention to the aged one, looking for the control and modification of the intrinsic and ambient factors of risk potentially you prevented.